1973
DOI: 10.1111/j.1748-1716.1973.tb05529.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Temperature on Steady State Ventilation and Metabolism in Exercise

Abstract: Petersen, E. S. and H. Vejby‐Christensen. Effect of body temperature on steady state ventilation and metabolism in exercise. Acta physiol. scand. 1073. 89. 342–351. Four healthy subjects were studied at rest and during steady slate of work at normal room and body temperature, and at elevated body temperature (38.5o C) in a climatic chamber. Ventilation, oxygen uptake, carbon dioxide elimination, heart rate, and blood lactate and pyruvate concentrations were measured. At equal work loads ventilation was not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 24 publications
4
10
1
Order By: Relevance
“…3) is in agreement with results from previous studies (2,25). Petersen and Vejby-Christensen (25) suggested that a core temperature threshold for ventilation existed around 38°C above which a significant hyperpnea was evident.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…3) is in agreement with results from previous studies (2,25). Petersen and Vejby-Christensen (25) suggested that a core temperature threshold for ventilation existed around 38°C above which a significant hyperpnea was evident.…”
Section: Discussionsupporting
confidence: 83%
“…3) is in agreement with results from previous studies (2,25). Petersen and Vejby-Christensen (25) suggested that a core temperature threshold for ventilation existed around 38°C above which a significant hyperpnea was evident. These core temperature thresholds were subsequently defined for passively or actively induced hyperthermia (2,37), and above these thresholds, ventilation increased proportionately to core temperatures (2,37).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations